Tratamiento farmacológico de pacientes con insuficiencia cardíaca crónica. Subanálisis de un registro ecuatoriano - Moreno-Rondón, Luis (2025)
Introduction. Introduction. In Ecuador, there is limited data on the treatment of patients with heart failure (HF). Objective. This study aimed to determine the rate of use of prognosis-modifying drugs and their association with prognosis. Materials and methods. A retrospective observational study was conducted on patients with chronic HF included in the “Los Ceibos” registry between January 2017 and December 2022. Patients were followed for a median of 2.28 years (interquartile range [IQR]: 1.25-3.49). Results. A total of 711 patients diagnosed with HF were included. Among them, 82.7% (n=588) received angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), or angiotensin receptor–neprilysin inhibitors (ARNIs); 82.3% (n=585) received beta-blockers (BBs); and 51.3% (n=365) were treated with mineralocorticoid receptor antagonists (MRAs). Among patients with HFrEF, those receiving triple therapy (ACEI/ARB/ARNI + BB + MRA) had lower all-cause mortality compared to other groups (38.8%, log-rank p=0.014). In patients with Heart Failure with preserved Ejection Fraction (HFpEF), no mortality differences were observed according to the number of medications used (log-rank p=0.720). MRA use was not associated with a prognostic benefit in HFpEF (p>0.05). Patients receiving triple therapy with ARNI + BB + MRA had better survival during follow-up compared to any other drug combination (log-rank p=0.027). Conclusions. A high rate of ACEI/ARB/ARNI and BB use was observed. The use of triple therapy, particularly the combination of ARNI + BB + MRA, was associated with improved prognosis in patients with HFrEF over a four-year follow-up period. No prognostic benefit of MRA use was observed in patients with HFpEF.